Membangun Kerja Sama Pemimpin di Sekolah Kristen: Perspektif Teologis atas Hambatan dan Solusinya - Suparman, Suparman (Diligentia: Journal of Theology and Christian Education, 2025)
Collaboration among leaders is a foundational aspect of leadership in Christian schools, rooted in the unity of the body of Christ. However, such collaboration does not occur automatically and is often hindered by personality differences, unstable faith, and divergent goals or personal interests. This article aims to analyze the obstacles to cooperation among leaders in Christian school settings by examining biblical narratives and proposing solutions from a theological perspective. Using a reflective-theological approach and current literature, this article highlights that Christian collaboration is not merely an administrative strategy, but an expression of koinonia—a fellowship that mirrors the loving relationship within the Triune God. Proposed solutions include spiritual and character formation, spiritual mentoring, restorative conflict resolution, and reaffirming a shared vision. These insights are intended to foster a more authentic and transformative model of Christian leadership within educational communities.